Association between Frailty and Dialysis Symptom Index among Chronic Hemodialysis Patients in Indonesia - Jeremia Immanuel Siregar; Hosea Glory (PT Dexa Medica, 2026)
Background: Chronic kidney disease (CKD) is a major cause of global mortality, with 79% of cases classified as stage G3-G5, making hemodialysis a common necessity. However, patients undergoing hemodialysis are at high risk of experiencingside effects, particularly frailty. Frailty, in turn, may worsen the side effects of hemodialysis and increase the risk of mortality. Therefore, this study aimed to investigate the association between frailty and the Dialysis Symptom Index in chronichemodialysis patients. Methods: This research used a cross-sectional method with an unpaired numerical comparative analytical study design. Data was obtained using the Dialysis Symptom Index (DSI) questionnaire and RAPUH questionnaire. Population of the study consisted of patients aged 18 years and older undergoing chronic hemodialysis. Statistical analysiswas performed using t-test or Mann-Whitney test, as appropriate. Results: There were 35 (24.8%) patients undergoing hemodialysis who experienced frailty and 106 (75.2%) patients undergoing hemodialysis who did not experience frailty. Frail patients exhibited significantly higher prevalence of the following symptoms: lack of appetite (p<0.001), shortness of breath (p=0.039), lightheadedness or dizziness (p=0.022), feeling tired or lack of energy (p<0.001), dry mouth (p=0.004), bone or joint pain (p=0.001), difficulty sleeping (p=0.014), easily awakened (p=0.007), decreased sexual desire (p<0.001), and difficulty becoming aroused sexually (p<0.001). Conclusion: This study demonstrated a significant associationbetween frailty and the side effects of hemodialysis. The most prevalent symptoms among frail patients included feeling tired or lack of energy, decreased sexual desire, difficulty becoming sexually aroused, easily awakened, muscle cramps, and difficulty sleeping.